Status and influencing factors of nurses’ organizational silence in general hospitals in eastern coastal cities of China - Xiangyan Lv; Yujia Gu; O. Mensah Solomon; Ying Shen; Yaxin Ren; Yehong Wei (BMC Nursing)
Abstract AIMS This study investigated the status and influencing factors of organizational silence among 624 nurses in general hospitals in eastern coastal cities of China. Methods This study followed STROBE guidelines. During the period from January to April 2024, the researchers investigated 624 clinical in-service nurses in terms of general information, employee silence behavior, work engagement, and peer support, and analyzed the related factors affecting nurses’ organizational silence. Results The total average score of nurses’ organizational silence was (33.88 ± 6.88), and the total score of work engagement was (69.23 ± 10.76); The total score of the colleague support scale was (90.02 ± 13.72), which was at the medium level. Univariate analysis showed that the scores of organizational silence of 610 nurses had statistical differences in departments, employment methods and professional titles (P < 0.05); Pearson correlation analysis showed that nurses’ work engagement (r=-0.530, P < 0.05), perceived colleague support a scale (r=-0.530, P < 0.05), colleague support B scale (r=-0.363, P < 0.05) were negatively correlated with organizational silence; Multiple linear regression analysis showed that department (β’value = 0.256, P = 0.001), employment mode (β’value = 0.115, P = 0.001), professional title (β’value = 0.741, P = 0.023), working years (β’value = 1.1110, P = 0.000), work engagement (β’value6.182, P = 0.000), colleague support scale A (β’value = 0.198, P = 0.003), and scale B (β’value = 0.485, P = 0.001) were the main influencing factors of nurses’ organizational silence behavior. Conclusions In this study, nurses’ organizational silence is at the medium level, and nursing workers with low outpatient service, contract system, professional title and working years, less work investment and poor support from colleagues are prone to silence behavior.